Improving beef cattle through breeding - Smith, W.H.; Schalles, R. (Kansas Agricultural Experiment Station, 2011)
The purebred Shorthorn cattle breeding project was continued during 1966 according to the original breeding program. Two inbred lives were established in 1949. The Wernacre Premier line is now in the fifth generation of inbreeding and the Mercury line, in the third generation. Inheritance of production traits in beef cattle are studied to evaluate effects of inbreeding and to explore the feasibility of using inbred lines to improve production traits of beef cattle.
Keywords: Beef; Production; Ration